KEBAN BARAJ GÖLÜNDE YAŞAYAN GLYPTOTHORAX TÜRLERİNDE KEMİKSİ YAPILARDAN KARŞILAŞTIRMALI YAŞ TAYİNİ - AKTAŞ, AYHAN (Fırat Üniveristesi, 2008)
Bu çalışma, Keban Baraj Gölü'nde yakalanan Glyptothorax armeniacus (Berg, 1918) ve Glyptothorax kurdistanicus (Berg, 1931) türlerinde Mayıs 2007- Temmuz 2008 tarihleri arasında yaş tayini için en uygun kemiksi yapıyı belirlemek amacıyla yapılmıştır. Balıklardan alınan otolit ( sağ ve sol), omur, pektoral yüzgeç ışını ( sağ ve sol), dorsal yüzgeç ışını, operkül ( sağ ve sol) örnekleri incelenmiş ve yaş tayini yapılmıştır. Karşılaştırmalı yaş tayini 8 kemiksi oluşumda yapılmış ve sonuçlar %N olarak tablolarla ifade edilmiştir. Her bir yapı bir okuyucu tarafından üç kez okunmuştur.Sonuç olarak her iki türde de en fazla uyumun, en küçük yaş tayini hata payı ve değişim katsayısının sağ otolitte olduğu saptanmıştır. Bu nedenle bu türlerde yaş tayini için en uygun kemiksi yapının sağ otolit olduğu sonucuna varılmıştır

In this study, it was aimed to determine the best suitable bony structure for age determination in Glyptothorax armeniacus (Berg, 1918) and Glyptothorax kurdistanicus (Berg, 1931) species obtained from Keban Dam Lake between May 2007 and July 2008. Otolit (right and left), vertebra, pectoral fin rays (right and left), dorsal fin ray and opercula (right and left) bony structures were removed and examined for age determination. Comparative age determinations were made from 8 bony structures and the results were given as N% in tables. The age of each bony structure was read 3 times by a reader.In conclusion, the best harmony with the smallest error rate and coefficient of variation was found im the right otoliths for both species. Fort this reason, it was concluded that the best suitable bony structure for age determination for these fish species was right otoliths.
Comparative age determination from bony structures in Glyptothorax species living in Keban dam lake
Keywords: Su Ürünleri